2020
DOI: 10.1017/sjp.2020.31
|View full text |Cite
|
Sign up to set email alerts
|

It Must have been Burnout: Prevalence and Related Factors among Spanish PhD Students

Abstract: Recent studies in different countries indicate that PhD students are more vulnerable to psychological disorders compared to the general population. No such data are available for the Spanish population. This study addresses this issue by studying prevalence rates and factors related to a common response to prolonged stress such as burnout syndrome. Burnout, emotional abilities, resilience, satisfaction with the dissertation advisor, and sociodemographic data were collected from 305 PhD students. The results in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 33 publications
0
13
0
6
Order By: Relevance
“…This group also reported the highest perceived animal stress/pain levels, which also showed a negative correlation with professional quality of life. This result may not be related solely to their work with laboratory animals, since different studies reported high levels of burnout and a poor work–life balance among biomedical PhD students worldwide [ 26 , 27 ] and in Spain [ 28 ]. Moreover, this poorest quality of life can be a risk factor for developing common psychiatric disorders, especially clinical depression [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…This group also reported the highest perceived animal stress/pain levels, which also showed a negative correlation with professional quality of life. This result may not be related solely to their work with laboratory animals, since different studies reported high levels of burnout and a poor work–life balance among biomedical PhD students worldwide [ 26 , 27 ] and in Spain [ 28 ]. Moreover, this poorest quality of life can be a risk factor for developing common psychiatric disorders, especially clinical depression [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…We observed a shared feeling that the advancement in scientific careers is today based on problematic aspects of the same, where some peers could potentially engage in QRPs as a means for ensuring publications and job security. Moreover, we are just starting to understand how this structure could impair mental health, particularly among young researchers (Sorrel et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Doctoral emotional wellbeing has been evaluated in doctoral populations through variables such as mental health, absence of anxiety, stress or depression symptoms, themselves measured with clinically-validated self-report instruments like the DASS-21, GHQ-12, PHQ-9 or GAD-7 (e.g., in Evans et al, 2018;Barry et al, 2019;Levecque et al, 2017;Marais et al, 2018). In addition, academic stress or burnout has been specially related, in the context of the doctorate, with emotional wellbeing problems (e.g., Sorrel et al, 2020) and intentions to drop out (Peltonen et al, 2017) or leave academia (Devine & Hunter, 2016). In this sense, aside from generic burnout scales from organizational psychology, Cornér and colleagues at the University of Helsinki ( 2017) have developed an 8-item burnout scale specifically for doctoral student populations.…”
Section: Related Work Dropout and Emotional Wellbeing In Doctoral Studiesmentioning
confidence: 99%